Ocupação da terra e uso de recursos naturais em uma comunidade de agricultores familiares da Transamazônica - SOUSA, Maria Adilane da Conceição (2023)
It is considered that the development model that predominates in the Amazon is characterized by deep social inequality. A viable solution for the sustainability of the region is family farming. Aiming to contribute to the understanding of its importance for Amazonian populations, the present work analyzes the history of occupation of a community and the coexistence with the forest. The study area is the community Nossa Senhora Imaculada da Conceição, Altamira - PA. It was studied, between 2019 and 2023, by participant observation, documentary research, and interviews with residents. Its foundation occurred in the 1970s, under the influence of the Transamazonic Highway's inauguration. Old residents reported that, when they arrived in the territory, there was the presence of indigenous people, who moved away from there during the demarcation of lots. In the 1990s, INCRA gave the settled families access to some public policies. Even so, several difficulties caused many of them to give up, among which were the precarious conditions of access. The residents who persisted cultivated, initially, rice, beans and corn. Nowadays it is common to plant cocoa, açai, coconut, and banana trees. Replacement planting of fruit trees is also common. Plants of extractive interest with origins in the forests mentioned were: açai (Euterpe oleracea), bacaba (Oenocarpus bacaba), Brazil nut tree (Bertholletia excelsa) and andiroba (Carapa guianensis). Among the mammals mentioned are: giant anteater (Myrmecophaga tridactyla), guariba (Alouatta sp.), jaguar (Panthera onca), white-lipped peccary (Tayassu pecari) and paca (Cuniculus paca). In addition, residents pointed out the occurrence of 36 ethnospecies of wild birds and 15 of stream fish. The community is home to a mosaic of landscapes, including ecological corridors between forested areas, which are fragmented by pastures. Therefore, family farming promotes the livelihood of portions of the society and preserves samples from the Amazon biodiversity.